2011
DOI: 10.4103/0019-5413.87133
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of tendon transfer for radial nerve paralysis: Comparison of three methods

Abstract: Background:Tendon transfer for radial nerve paralysis has a 100 years history and any set of tendons that can be considered to be useful has been utilized for the purpose. The pronator tress is used for restoration of wrist dorsiflexion, while the flexor carpi radialis, flexor carpiulnaris, and flexor digitorum superficialis are variably used in each for fingers and thumb movements. The present study was a retrospective analysis, designed to compare three methods of tendon transfer for radial nerve palsy.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The essential consideration is the avoidance of radial deviation of the wrist by centralizing the insertion of the ECRL [ 62 ]. The Merle d'Aubigne and Lance procedure is reported to be an excellent and reliable method; two retrospective studies revealed that 73,2 - 88,4% of treated patients were able to return in their original occupations 4 months after surgery [ 63 , 64 ]. However, this procedure is also not free of any problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential consideration is the avoidance of radial deviation of the wrist by centralizing the insertion of the ECRL [ 62 ]. The Merle d'Aubigne and Lance procedure is reported to be an excellent and reliable method; two retrospective studies revealed that 73,2 - 88,4% of treated patients were able to return in their original occupations 4 months after surgery [ 63 , 64 ]. However, this procedure is also not free of any problems.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important wrist movement, which is necessary for activities such as hammering and throwing [ 58 ]. Additionally, the ability to simultaneously extend the wrist and long fingers II-V cannot be achieved in most of patients treated by triple transfer procedures, whereas the majority of patients are able to move their fingers separately [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall result was rated as perfect, good, fair, or poor according to the Moussavi et al [10] classification. The assessment criteria are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Various transfers of tendons have been described for this condition, one of the most common types of reconstruction utilizes the pronator teres muscle for wrist extension, the palmaris longus muscle for thumb extension and abduction and the flexor carpi ulnaris muscle to regain finger extension. These transfers yield good functional results with relatively little donor-site morbidity ( 25 , 26 ). Although the muscles that can be used vary greatly between patients and their individual patterns of functional loss, the principle of replacing lost muscle function by the transfer of still working muscles remains valid and can be applied for various conditions.…”
Section: Functional Reconstructionmentioning
confidence: 99%